2012
DOI: 10.5539/gjhs.v4n5p147
|View full text |Cite
|
Sign up to set email alerts
|

The Isoflavone-Rich Fraction of the Crude Extract of the Puerariae Flower Increases Oxygen Consumption and BAT UCP1 Expression in High-Fat Diet-Fed Mice

Abstract: Puerariae flower extract (PFE) is a crude extract of the Kudzu flower. Previous studies have shown that PFE supplementation exerts anti-obesity and anti-fatty liver effects in high-fat diet-fed mice. In this study, we aimed to identify the PFE components responsible for these effects and to determine their influence on energy expenditure and uncoupling protein 1 (UCP1) expression. Experiments were conducted on C57BL/6J male mice classified into 3 groups: (1) high-fat diet-fed (HFD), (2) high-fat diet-fed given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
1
28
2
Order By: Relevance
“…High-fat diets are widely used to induce obesity in animal experiments (Kamiya et al, 2012;Maeda et al, 2009;Nishi et al, 2007;Yamasaki et al, 2013). The high-fat diet experimental period in the present study induced a marked weight increase.…”
Section: Adrb3 Plays An Important Anti-obesity Role Because Its Agonistsmentioning
confidence: 52%
See 2 more Smart Citations
“…High-fat diets are widely used to induce obesity in animal experiments (Kamiya et al, 2012;Maeda et al, 2009;Nishi et al, 2007;Yamasaki et al, 2013). The high-fat diet experimental period in the present study induced a marked weight increase.…”
Section: Adrb3 Plays An Important Anti-obesity Role Because Its Agonistsmentioning
confidence: 52%
“…Yamasaki et al (2013) reported that C57/BL mice fed high-fat diet with a wasabi leaf hot-water extract (without specific pungent components such as allyl isothiocyanate) showed anti-obesity effects. Furthermore, polyphenols are known for their anti-obesity effects (Kamiya et al, 2012;Nishi et al, 2007). Misawa et al (2015) reported that polyphenols contained in wasabi leaves Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that PFE exerts anti-obesity effects in humans and mice fed high-fat diets [2][3][4]. In addition, we also reported that the isoflavone-rich fraction of dietary PFE exhibits anti-obesity effect in mice fed high-fat diets [5].…”
Section: Introductionmentioning
confidence: 99%
“…The following isoflavones are found in the Kudzu flower but not in soy: 6-hydroxygenistein 6,7-di-O-glucoside (6HGDG), tectorigenin 7-O-xylosylglucoside (TGXG), tectoridin, genistin, glycitin, tectorigenin, genistein, and glycitein [5]. Among these isoflavones, 6HGDG, TGXG, tectoridin and tectorigenin, which comprise nearly 90% of the isoflavones in the Kudzu flower, are present in PFE.…”
Section: Introductionmentioning
confidence: 99%